Fake Accounts on Social Media as a Criminal Act of Electronic Information Manipulation in Indonesia - Rezky, Michelle; Ibrahim, Aji Lukman (Universitas Airlangga, 2022)
There are often cases where irresponsible individuals create social media accounts using other people's personal identities as if the account is the original account of the person whose identity is being used, hereinafter referred to as fake social media accounts. Such actions can be threatened with Article 35 jo. Article 51 paragraph (1) of Law Number 11 of 2008 concerning Information and Electronic Transactions (ITE Law). The type of research used by the author in this study is prescriptive normative law research with a statute approach and a case approach. In Verdict Number 1739/Pid.Sus/2020/PN Jkt.Brt, the defendant was declared guilty of committing a crime under Article 28 paragraph (1) jo. Article 45A paragraph (1) ITE Law. Not only fulfilling the elements in Article 28 paragraph (1) of the ITE Law, but the defendant also fulfilled the elements in Article 35 of the ITE Law. However, the defendant was not found guilty of a criminal offense under Article 35 of the ITE Law, even though Article 35 of the ITE Law was one of the prosecutor's indictments. Based on this research, the defendant was not found guilty of a criminal offense under Article 35 of the ITE Law because the form of the indictment in Verdict Number 1739/Pid.Sus/2020/PN Jkt.Brt is less precise. The form of indictment used by the public prosecutor is an Alternative Indictment where ideally the public prosecutor ought to use Cumulative Indictment on a concursus realis crime that the defendant committed.